Long-Term Soy Protein Isolate Consumption Reduces Liver Steatosis Through Changes in Global Transcriptomics in Obese Zucker Rats - Kozaczek, Melisa; Bottje, Walter; Kong, Byungwhi; Dridi, Sami; Albataineh, Diyana; Lassiter, Kentu; Hakkak, Reza (Frontiers in Nutrition, 2020)
To determine how soy protein isolate (SPI) ameliorated liver steatosis in male obese Zucker rats, we conducted global transcriptomic expression (RNAseq) analysis on liver samples of male rats fed either the SPI or a control casein (CAS)-based diet (n = 8 per group) for 16 weeks. Liver transcriptomics were analyzed using an Ilumina HiSeq system with 2 × 100 base pair paired-end reads method. Bioinformatics was conducted using Ingenuity Pathway Analysis (IPA) software (Qiagen, CA) with P < 0.05 and 1.3-fold differential expression cutoff values. Regression analysis between RNAseq data and targeted mRNA expression analysis of 12 top differentially expressed genes (from the IPA program) using quantitative PCR (qPCR) revealed a significant regression analysis (r2 = 0.69, P = 0.0008). In addition, all qPCR values had qualitatively similar direction of up- or down-regulation compared to the RNAseq transcriptomic data. Diseases and function analyses that were based on differentially expressed target molecules in the dataset predicted that lipid metabolism would be enhanced whereas inflammation was predicted to be inhibited in SPI-fed compared to CAS-fed rats at 16 weeks. Combining upstream regulator and regulator effects functions in IPA facilitates the prediction of upstream regulators (e.g., transcription regulators) that could play important roles in attenuating or promoting liver steatosis due to SPI or CAS diets. Upstream regulators that were predicted to be activated (from expression of down-stream targets) linked to increased conversion of lipid and transport of lipid in SPI-fed rats included hepatocyte nuclear factor 4 alpha (HNF4A) and aryl hydrocarbon receptor (AHR). Upstream regulators that were predicted to be activated in CAS-fed rats linked to activation of phagocytosis and neutrophil chemotaxis included colony stimulating factor 2 and tumor necrosis factor. The results provide clear indication that long-term SPI-fed rats exhibited diminished inflammatory response and increased lipid transport in liver compared to CAS-fed rats that likely would contribute to reduced liver steatosis in this obese Zucker rat model.